Penerapan Model Pembelajaran Kooperatif Two Stay Two Stray Untuk Meningkatkan Kemampuan Komunikasi Matematis Siswa Pada Materi Koordinat Kartesius di Kelas X - Tutiarny Naibaho; Bajongga Silaban; Susi Sihombing (IKIP PGRI Bojonegoro, 2023)
Abstract: This study aims to determine the increase in students' mathematical communication skills on Cartesian coordinate material in class X SMA N 1 Pagaran. This type of research is Classroom Action Research (PTK) with the subjects in the study namely students in class X SMA N 1 Pagaran with a total of 20 students. This research was conducted only in one class. The instruments used were post-test 1 and post-test 2 in the form of essays that had been tested for instrument validation and student and teacher observation sheets. After different treatments, the results of observations of student activity during the learning process were obtained, namely 75.5% in the active category, the results of observations of teacher activity during the learning process, namely 3.3 in the very good category, achieved individual student learning completeness by obtaining the proportion of correct answers at least moderate or 65%, the achievement of student learning mastery in a classical manner, namely there are 85% of students obtaining student learning mastery individually at least moderate or 65%, there is an average increase in the percentage of students' mathematical communication in Cycle I, namely 58.65 and Cycle II, namely 76,565. This means that the learning carried out has been successful, so it can be concluded that the Two Stay Two Stray learning model can improve students' mathematical communication on Cartesian coordinate material in class X SMA N 1 Pagaran. Keywords: Model, Cooperative Two Stay Two Stray, Mathematical Communication. Abstrak: Penelitian ini bertujuan untuk mengetahui peningkatan kemampuan komunikasi matematis siswa pada materi koordinat kartesius di kelas X SMA N 1 Pagaran. Jenis penelitian ini adalah PenelitianTindakan Kelas (PTK) dengan Subjek dalam penelitian yaitu siswa di kelas X SMA N 1 Pagaran dengan jumlah siswa 20 orang. Penelitian ini dilakukan hanya pada satu kelas. Insturmen yang digunakan adalah post tes 1 dan post tes 2 dengan bentuk esai yang telah dilakukan uji validasi intrumen serta lembar observasi siswa dan guru. Setelah dilakukan perlakuan yang berbeda, diperoleh hasil observasi aktivitas siswa saat proses pembelajaran yaitu 75.5% dalam kategori aktif, hasil observasi aktivitas guru saat proses pembelajaran yaitu 3.3 dalam kategori sangat baik, tercapainya ketuntasan belajar siswa secara individual dengan memperoleh proporsi jawaban benar paling sedikit sedang atau 65%, tercapainya ketuntasan belajar siswa secara klasikal yaitu terdapat 85% siswa memperoleh ketuntasan belajar siswa secara individual paling sedikit sedang atau 65%, terdapat pertambahan rata-rata persentase komunikasi matematis siswa pada siklus I yaitu 58.65 dan siklus II yaitu 76.565. Hal ini berarti pembelajaran yang dilaksanakan telah berhasil, maka dapat disimpulkan bahwa model pembelajaran Two Stay Two Stray dapat meningkatkan komunikasi matematis siswa pada materi koordinat kartesius di kelas X SMA N 1 Pagaran. Kata Kunci: Model, Kooperatif Two Stay Two Stray, Komunikasi Matematis